Perception About the Role of Anesthesia and Anesthesiologist Among the Paramedical Staffs: Perspective from a Medical College in Nepal - Bhattarai, B; Kandel, S; Adhikari, N (Kathmandu University Medical Journal, 2013)
Background Anesthesiologists and anesthesia has been considered behind the scene. The image and status of anesthesiologist in the eyes of the medical and lay communities has always been a problem. Objectives This study was designed to assess the knowledge about the role of anesthesiologist among the paramedical staffs at Kathmandu University Hospital. Methods This prospective questionnaire based study was done at Kathmandu University School of Medical Science, Dhulikhel Hospital for 2nd January 2011 to 30th Jan 2011 among the paramedical staffs working in different department of the hospital. Results There were 150 questionnaire distributed out of which 120 responded. Mean Age was 23.33 and most of the respondents were female with majority having education qualification equivalent to intermediate level. Only 49.20 said it to be a different specialty and 72.5% said anaesthesiologist work differently in the theatre where as 70% knew anaesthesiologist did something in the post-operative period too. Conclusion Anesthesiologists have duty to visit patient’s pre operatively and post operatively. The role inside the theatre and expanding role outside the theatre is poorly known. The awareness about the role of anesthesiologist in operation theatre, in intensive care unit, acute and chronic pain management and emergency care areas should be highlighted to all the staffs. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 51-54 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7344